Emerging Trends of TV Talk Shows and Increasing Frequency of Political Discussion: Content Analysis on Talk Shows of Leading Pakistani News Channel - Malik, Muhammad Raees (American Journal of Humanities and Social Sciences, 2018)
Inception of talk shows has revolutionized the information for all age viewers to political/ regional/ extra regional challenges (just a click away). Besides connecting the talk shows viewers to one TV channel, another objective of these Talk shows is to sell the particulars responsible and literary persons own views and comments regarding the on going and current hot issue or particular matter. Till now the concluded results of these Talk shows are more likely to maintain centric approach rather broad approach with regard to strengthen Social Capacity Building(SCB) in all field of life. Present study main focus is just to know that which type of issues are being discussed in these talk shows and which type of impact these talk shows have on the Pakistani people. its another focus is identify that if we found some sort of gaps which these talk shows are not fullfilling so either we can achieve those set goals and objectives or not to improve the objectives of these talk shows. if the Talk Shows planners revisit their ongoing strategies a social and cultural change can be brougt in these talk shows regarding these concerned i.e. political, education, health, law & orders, religious etc. following are the gaps which researcher have identified in these talk shows and those are: Limited information regarding the focused topic which is discussed during these talk shows on Pakistani TV channels. Talk shows mainly focus on the important issues and challenges, with respect to Historic and Future aspect of any situation are left over which are not discussed during the discussion due to biasness or tv channel polices so which creat a gap for idenifying the meaning full information. Due various controllable and controllable limitations; today talk shows are seem to maintain reactive response rather than Pro-active.